-3(2y-4)=6y

Simple and best practice solution for -3(2y-4)=6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2y-4)=6y equation:



-3(2y-4)=6y
We move all terms to the left:
-3(2y-4)-(6y)=0
We add all the numbers together, and all the variables
-6y-3(2y-4)=0
We multiply parentheses
-6y-6y+12=0
We add all the numbers together, and all the variables
-12y+12=0
We move all terms containing y to the left, all other terms to the right
-12y=-12
y=-12/-12
y=1

See similar equations:

| -4x-5=x-35 | | 3x+13=11x-1 | | 0.3-4y=10 | | x+10=3x+32* | | 12=n+-7 | | a+120=200 | | 14x+3+14x-19=180 | | 3x-2x+4=1+x+3 | | Y=200,000/x | | 7x-76=5x-32 | | 3/4•f=6 | | 20x-36+2x=-10+3x-7 | | r+50=120 | | 45y=22(2y+1) | | (180-x)+90-×)=210 | | (x-5)/3+(3x-1)/2=5 | | 34+3x+12x-34=180 | | 2(5y+12)=18y | | 17x^2+48x+9=0 | | 14x+13x-9=180 | | -9+8p=-7 | | x^2-7=20 | | 14b=-18 | | x-40=40 | | 14x=13x-9 | | 13=2x+6+6x-6 | | x^2+5x+6=9x+3 | | 6x^-5x=17 | | 36c=1116 | | 64x-3+26x+3=180 | | 2x+6+13=6x-6 | | b-40=90 |

Equations solver categories